Adsorption behaviour and mechanisms of cadmium and nickel on rice straw biochars in single- and binary-metal systems - Deng, Yiyi; Huang, Shuang; Laird, David A.; Wang, Xiugui; Meng, Zhuowen (Chemosphere (Oxford), 2019)
Adsorption mechanisms and competition between Cd2+ and Ni2+ for adsorption by rice straw biochars prepared at 400 °C (RB400) and 700 °C (RB700) were investigated in this study. Based on the Langmuir model, the maximum adsorption capacities (mg g−1) of Cd2+ and Ni2+ on RB400 and RB700 were in the order of Cd2+ (37.24 and 65.40) > Ni2+ (27.31 and 54.60) in the single-metal adsorption isotherms and Ni2+ (25.20 and 32.28) > Cd2+ (24.22 and 26.78) in the binary-metal adsorption isotherms. Cd2+ competed with Ni2+ for binding sites at initial metal concentrations >10 mg L−1 for RB400 and > 20 mg L−1 for RB700. The adsorption sites for Cd2+ and Ni2+ on the biochars largely overlapped, and the binding of Cd2+ and Ni2+ to these sites was affected by the occupation sequence of these metals. For Cd2+ and Ni2+ adsorption in the binary system, cation exchange and precipitation were the dominant adsorption mechanisms on RB400 and RB700, respectively, accounting for approximately 36% and 60% of the adsorption capacity. Competition decreased the contribution of cation exchange but increased that of precipitation and other potential mechanisms. Results from this study suggest that types and concentrations of metal ions should be taken into account when removing metal contaminants from water or soil using biochars. [Display omitted] •The adsorption sites for Cd2+ and Ni2+ on the biochars largely overlapped.•Rice straw biochars exhibited adsorption preferences for Ni2+ over Cd2+ when coexisted.•Competition occurred once the concentrations of Cd2+ and Ni2+ exceeded the threshold values.•Competition between Cd2+ and Ni2+ decreased the adsorption amounts but increased the mobility.•Competition between Cd2+ and Ni2+ decreased the contribution of cation exchange mechanism.